VIDA NO CAMPUS: SOCIABILIZAÇÃO ATRAVÉS DO ESPORTE E DO LAZER - Baptista, Juliana B.; Noll, Gisele C.; Flora, Jéssica P. D.; Bertollo, Mauro; Jendrzyczkowski, Quele R.; Göller, Dari F. (Salão do Conhecimento, 2013)
Resumo